Avaliação imunohistoquímica da expressão de receptores estrogênicos alfa e progesterona no carcinoma diferenciado de tireóide - Martins, Mayane Emanuela Melo Lopes (2015)
With the use of sensitive imaging methods, there is an increase in thyroid nodules diagnosed. Even the CDT (differentiated thyroid cancer) being proportionately rare, its incidence is increasing, especially small tumors whose clinical outcome is uncertain. It is observed that in clinical practice most patients with CDT develops well when properly treated, mortality rates similar to the general population. On the other hand, a non-negligible percentage has relapses and some eventually not respond to conventional therapies, and died. It can be seen that with the need to identify markers that can predict the behavior of tumors, mainly due to the variable clinical disease progression. With these data, some researchers in search of these markers, are studying a possible relationship of hormonal and reproductive factors in the evolution of CDT. This study analyzes the immunoreactivity of α estrogen receptor (ERα) and progesterone receptor (PR), correlating it with clinical features in 80 female and male patients with papillary thyroid cancer (PDT) and follicular thyroid cancer (FDT ) with materials related to thyroidectomy pieces performed at the University Hospital Walter Cantídio (HUWC) in the period from 2010 to 2014. There was a predominance of female patients (87.5%), older than or equal to 40 years (68.57%), average age 49.12, tumor size> 1 cm (69.04%), papillary histological type (95.24%), with location in one wolf, not multicenter, (61.90 %), lack of angiolymphatic invasion (67.85%), absence of invasion of the capsule (75%) without Hashimoto's thyroiditis (73.80%). In adjacent normal tissues it was observed that ER expression (77.77%) is greater than the PR expression (47.05%). In tumors observed the opposite, ERα (43.75%) and PR (47.5%) with a higher PR expression, these data were correlated with the clinical characteristics of tumors, such as gender, tumor size, age the diagnosis, capsular invasion, lymphatic invasion, Hashimoto's thyroiditis, tumor location, histological type and variants.